Curricular Changes and Teacher Performance: between duty and power to act - Adonías Julia Villa Calderón; Edwin Daniel Félix-Benites; Uriel Montes Serrano; William Camilo Yauris Polo (Educação & Realidade)
The objective of this study was to analyze the perception of secondary school Communication teachers regarding the impact of curricular changes on teaching performance in schools in the province of Andahuaylas, Peru, 2022. Qualitative, descriptive and analytical study. The results indicate that the construction of categories of meaning from the teachers’ narratives characterized the experience of curriculum implementation as a dynamic and complex process. The constructs “curricular change” and “learning” turned out to be core categories that structure the participants’ experience. The search for answers to the changes unfolds in permanent tension due to the collision between the vocation for teaching and the limitations of the context.